To solve the equation -3x - 9 = -21, you need to isolate the variable x. Let's go step by step:
Step 1: Add 9 to both sides of the equation to eliminate the constant -9 on the left side:
-3x - 9 + 9 = -21 + 9
-3x = -12
Step 2: Divide both sides of the equation by the coefficient -3 to isolate the variable x:
(-3x)/(-3) = (-12)/(-3)
x = 4
Therefore, the solution to the equation -3x - 9 = -21 is x = 4.
The equation -3x-9=-21
9 answers
The equation 10x+13=-12
To solve the equation 10x + 13 = -12, you need to isolate the variable x. Let's go step by step:
Step 1: Subtract 13 from both sides of the equation to eliminate the constant 13 on the left side:
10x + 13 - 13 = -12 - 13
10x = -25
Step 2: Divide both sides of the equation by the coefficient 10 to isolate the variable x:
(10x)/10 = (-25)/10
x = -2.5
Therefore, the solution to the equation 10x + 13 = -12 is x = -2.5.
Step 1: Subtract 13 from both sides of the equation to eliminate the constant 13 on the left side:
10x + 13 - 13 = -12 - 13
10x = -25
Step 2: Divide both sides of the equation by the coefficient 10 to isolate the variable x:
(10x)/10 = (-25)/10
x = -2.5
Therefore, the solution to the equation 10x + 13 = -12 is x = -2.5.
Solve 5-6x=-7
To solve the equation 5 - 6x = -7, you need to isolate the variable x. Let's go step by step:
Step 1: Subtract 5 from both sides of the equation to eliminate the constant 5 on the left side:
5 - 6x - 5 = -7 - 5
-6x = -12
Step 2: Divide both sides of the equation by the coefficient -6 to isolate the variable x:
(-6x)/(-6) = (-12)/(-6)
x = 2
Therefore, the solution to the equation 5 - 6x = -7 is x = 2.
Step 1: Subtract 5 from both sides of the equation to eliminate the constant 5 on the left side:
5 - 6x - 5 = -7 - 5
-6x = -12
Step 2: Divide both sides of the equation by the coefficient -6 to isolate the variable x:
(-6x)/(-6) = (-12)/(-6)
x = 2
Therefore, the solution to the equation 5 - 6x = -7 is x = 2.
The equation 5/3x+11/3=-4/3
To solve the equation (5/3)x + 11/3 = -4/3, you need to isolate the variable x. Let's go step by step:
Step 1: Subtract 11/3 from both sides of the equation to eliminate the constant 11/3 on the left side:
(5/3)x + 11/3 - 11/3 = -4/3 - 11/3
(5/3)x = -15/3
Step 2: Simplify the expression -15/3 on the right side:
(5/3)x = -5
Step 3: Multiply both sides of the equation by the reciprocal of (5/3), which is (3/5), to isolate the variable x:
(3/5)(5/3)x = (3/5)(-5)
x = -3
Therefore, the solution to the equation (5/3)x + 11/3 = -4/3 is x = -3.
Step 1: Subtract 11/3 from both sides of the equation to eliminate the constant 11/3 on the left side:
(5/3)x + 11/3 - 11/3 = -4/3 - 11/3
(5/3)x = -15/3
Step 2: Simplify the expression -15/3 on the right side:
(5/3)x = -5
Step 3: Multiply both sides of the equation by the reciprocal of (5/3), which is (3/5), to isolate the variable x:
(3/5)(5/3)x = (3/5)(-5)
x = -3
Therefore, the solution to the equation (5/3)x + 11/3 = -4/3 is x = -3.
The equation 0.24x-0.74=-1.1
To solve the equation 0.24x - 0.74 = -1.1, you need to isolate the variable x. Let's go step by step:
Step 1: Add 0.74 to both sides of the equation to eliminate the constant -0.74 on the left side:
0.24x - 0.74 + 0.74 = -1.1 + 0.74
0.24x = -0.36
Step 2: Divide both sides of the equation by the coefficient 0.24 to isolate the variable x:
(0.24x) / 0.24 = (-0.36) / 0.24
x = -1.5
Therefore, the solution to the equation 0.24x - 0.74 = -1.1 is x = -1.5.
Step 1: Add 0.74 to both sides of the equation to eliminate the constant -0.74 on the left side:
0.24x - 0.74 + 0.74 = -1.1 + 0.74
0.24x = -0.36
Step 2: Divide both sides of the equation by the coefficient 0.24 to isolate the variable x:
(0.24x) / 0.24 = (-0.36) / 0.24
x = -1.5
Therefore, the solution to the equation 0.24x - 0.74 = -1.1 is x = -1.5.